Evidence of interaction between genes in the folate/homocysteine metabolic pathway in controlling risk of non‐syndromic oral cleft. (24th April 2018) - Wang, P; Wu, T; Schwender, H; Wang, H; Shi, B; Wang, ZQ; Yuan, Y; Liu, DJ; Wang, MY; Li, J; Zhou, ZB; Zhu, HP; et al.
Abstract : Objective: Little consistent evidence is available for the association between the risk of non‐syndromic cleft lip with or without cleft palate (NSCL/P) and any of the individual genes in the folate/homocysteine metabolic pathway. We investigated the genes in the folate pathway to further clarify its potential influence on the risk of NSCL/P considering gene–gene (G×G) interaction. Subjects and methods: We selected markers in 18 genes from the pathway and applied Cordell's method to test for G×G interaction using 1, 908 NSCL/P case–parent trios ascertained in an international consortium where a genomewide association study (GWAS) of oral clefts was conducted. Results: We found intriguing signals among Asian and European ancestry groups for G×G interaction between markers in betaine‐homocysteine methyltransferase gene ( BHMT / BHMT2 ) and dimethylglycine dehydrogenase gene ( DMGDH) attaining genomewide significance. In the pooled data, the top significant interaction was found between rs13158309 ( BHMT ) and rs10514154 ( DMGDH, p  =   1.45 × 10 −12 ). Conclusions: Our study illustrated the importance of taking into account potential G×G interaction for genetic association analysis in NSCL/P, and this study suggested both BHMT / BHMT2 and DMGDH should be considered as candidate genes for NSCL/P in future studies.